The Application of The “One Day One Ayat” Method in Getting Used to Memory of Short Letters in Raudhatul Athfal's Students - Fajarini, Asniar (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
Instilling spiritual values ​​in early childhood is very important in order to form an Islamic character. Habituation that is religious in nature is repeated every day will make it easier for children to practice it in their daily lives. This one day one verse method makes it easier for a child, especially early childhood, to memorize short surahs where these short surahs are read in their daily life later, namely during the obligatory prayer service. This study uses field research, namely qualitative research with phenomenological studies. The purpose of the study was to describe one day one verse activities at RA (Raudhatul Athfal) Masyithoh 13 Sokaraja Lor and to find out the application of the one day one verse method by the teacher. Data were obtained through observation and interviews as well as field notes with data analysis using the Mills and Hubberman models. The research findings show that this one day one verse makes it very easy for children to memorize short letters, almost all of them can follow them well.